PERBEDAAN PENGARUH METODE LATIHAN DAN KOORDINASI MATA TANGAN TERHADAP KETERAMPILAN MEMUKUL BOLA SOFTBALL - FERI FITRIYANTO (Jurnal Ilmiah Spirit, 2014)
The purpose of this study was to obtain information about the effect of differences in training methods and coordination of eye - hand Against softball hitting skills. This study used an experimental method with 2 x 3 factorial design. Study population was 66 students are from students of Department of Sports and Health Education, Faculty of Teacher Training and Education, University of Tunas Pembangunan Surakarta. The study sample of 60 students with a purposive random sampling technique. Data collection techniques with hand-eye coordination test and test skills softball hitting skills. Engineering analysis using Analysis of Variance (ANOVA) at level Î± = 0.05 siqnifikansi. The results of the study were 1). There is a significant difference between the methods of tee ball drills and training methods soft tos ball to hit the ball soft ball skills with a p-value = 0.016 is less than 0.05, 2). There are significant differences between students who have good hand eye coordination, moderate, lacking the skills to hit the ball soft ball with a p-value = 0.49 is smaller than 0.05, 3). There is interaction between training methods and hand-eye coordination to hit the ball soft ball skills with p-value = 0.001 is less than 0.05. From the results of this study concluded that (1) Method tos soft exercise ball has better results in improving the skills of hitting the ball soft ball. (2) Students who have good hand eye coordination have improved outcomes compared with students who have the hand eye coordination medium and low. (3) There is an interaction between method latihna and hand-eye coordination to hit the ball soft ball skills. a). Students who have a moderate hand-eye coordination will be faster in improving the skills of hitting the ball soft ball when given training method tee ball. b). Students who have good hand-eye coordination will be faster in improving the skills of hitting the ball soft ball when given training method soft tos ball. c). Students who have good hand-eye coordination will be lower in improving the skills of hitting the ball soft ball when given training method tee ball or soft tos ball.